RESPON VIETNAM PASCA PEMBANGUNAN ANJUNGAN MINYAK TIONGKOK DI KEPULAUAN PARACEL TAHUN 2014 - Yudi M "; Idjang Tjarsono (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
This study analyzed the responses on how the post-Vietnam development of Tiongkok oil platforms in 2014. Paracel Islands is an island that is still contested by Vietnam with Tiongkok. The two countries claim is based on the historical record so that this conflict led to tensions in the South China Sea. The datas were collected from many sources like books, journals, and websites that can support this research. In this research, the researcher uses realism perspective to describe the responses on how the post-Vietnam development of Tiongkok oil platforms in 2014. This research is supported by decision maker theory and strateyi theory. Tiongkok to build oil platforms in the Paracel Islands although in the process of development opposed Vietnam by sending ships to repel the ships Tiongkok will operation, but Tiongkok still build oil rig that although finally had a collision of ships Vietnam with Tiongkok as well as a war water cannon in it secures the interests of each claimant country. After the successful development of the Tiongkok oil platforms, Vietnam demonstrated anti-Tiongkok and asked for support on international world to condemn the aggressive actions of Tiongkok in the South China Sea.Keywords : Anti-Tiongkok. Claim, Paracel Island, and Tiongkok oil platforms